Draft Genome Sequence of Streptomyces xinghaiensis (fradiae) OlgR, a Strain Resistant to Oligomycin A - Bekker, Olga B. (Microbiol Resour Announc, 2019)
We report a draft genome sequence of Streptomyces xinghaiensis (fradiae) OlgR, which is resistant to oligomycin A. This mutant strain is derived from S. xinghaiensis OlgR2.100, which is resistant to (33S)-azido-33-deoxyoligomycin A. We have identified single nucleotide polymorphisms (SNPs) in 7 genes, which may lead to oligomycin A resistance.